EcoPower Guardian in Mas Gading - Man Lung, Chong; Lai Mei Lan, Lenny; Anak Maoh, Mallinder (Multidisciplinary Applied Research and Innovation, 2025)
There are 105 Community colleges in Malaysia. It plays a vital role in providing technical and vocational training to students and offering lifelong learning opportunities to the community. However, these colleges face increasing operational costs, particularly in electricity expenses. For instance, Mas Gading Community College shows its electricity bill increase by RM 1633 from January to March 2024, highlighting the urgent need for more efficient energy management solutions. Despite various awareness campaigns aimed at reducing electricity consumption, these efforts have been ineffective due to human errors and inconsistent application of energy-saving measures. Therefore, to address this challenge, the EcoPower Guardian project proposes an innovative automatic light control system that controls using Internet of Things (IoT) technology. This system uses a timer-based mechanism, controlled by the ESP32 IoT board, to schedule lighting according to predefined timings. Additionally, it includes a manual override button for flexibility. The IoT integration allows for remote control and monitoring through the Arduino IoT Cloud, ensuring that lights are only used when necessary. As a result, the implementation of EcoPower Guardian lights saw a substantial 45% cut in power usage, resulting in annual electricity bill savings of RM368.28 and contributes to reduction in carbon emission as much as 0.93tCO2e annually. In conclusion, implementing the EcoPower Guardian in Mas Gading Community Colleges is a significant step towards addressing the critical issue of rising energy costs. The project promises substantial financial savings, technological innovation, and a strengthened commitment to sustainability. By integrating advanced IoT technology for energy management, community colleges can achieve consistent energy savings, improve financial stability, and promote environmental responsibility.